2007
DOI: 10.1038/ncpgasthep0837
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune pancreatitis

Abstract: Autoimmune pancreatitis is a rare systemic fibrotic inflammatory disorder that can affect organs such as the bile ducts, salivary glands, and retroperitoneal lymph nodes, in addition to the pancreas. Morphological characteristics of autoimmune pancreatitis include a diffusely enlarged 'sausage-shaped' pancreas and an irregularly narrowed duct of Wirsung. According to the revised Japan Pancreas Society criteria, the diagnosis of autoimmune pancreatitis requires that one or more secondary serologic or histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0
17

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 58 publications
0
61
0
17
Order By: Relevance
“…The spread of knowledge on AIP in the world promoted the recognition of this disease not only in Asian countries but also in Western countries [18][19][20][21][22]. Recently, an increasing number of case reports have been made from outside of Japan, confirming that this disease exists beyond regions and races.…”
mentioning
confidence: 95%
“…The spread of knowledge on AIP in the world promoted the recognition of this disease not only in Asian countries but also in Western countries [18][19][20][21][22]. Recently, an increasing number of case reports have been made from outside of Japan, confirming that this disease exists beyond regions and races.…”
mentioning
confidence: 95%
“…In a survey of 65 patients with autoimmune pancreatitis, HAMANO et al [11] reported hilar lymphadenopathy detected by CT scanning and gallium-67 scintigraphy to be the most frequent extrapancreatic lesion (80%). Other studies have identified intrathoracic lymphadenopathy in the majority of patients who undergo 18 F-fluoro-2-deoxy-D-glucose positron emission tomography [42,43].…”
Section: Mediastinal Diseasementioning
confidence: 99%
“…Studies published over the past few years have documented the association of a high serum IgG4 level with the characteristic lesion of dense lymphoplasmacytic infiltrates containing IgG4-positive plasma cells in various organs, including the bile duct (sclerosing cholangitis) [8][9][10][11], salivary gland (sclerosing sialadenitis) [2,[9][10][11], lacrimal gland (sclerosing dacryoadenitis) [2,10,11], liver (IgG4-hepatopathy) [2], kidney (inflammatory pseudotumour) [2,10], retroperitoneum (retroperitoneal fibrosis) [2,[9][10][11], aorta (inflammatory aneurysm) [2,12], and lymph nodes [2,9,13], as well as the lung [2,10,[14][15][16][17]. ISD can be localised to one or two organs or be present with diffuse systemic disease [1][2][3][18][19][20]. Furthermore, lesions in different organs can present simultaneously or metachronously.…”
mentioning
confidence: 99%
“…The former one is suspected to be the pancreatic lesions of IgG4-related diseases [4]. In type 1 AIP, most of the infiltrating cells in the pancreatic parenchyma are positive for IgG4 and the serum IgG4 levels are frequently elevated [5,6]. However, the role of IgG4 in the pathogenesis of AIP remains elusive.…”
Section: Introductionmentioning
confidence: 99%